REPRESENTATION OF INFLUENCER IDENTITY ON SOCIAL MEDIA (SOCIAL SEMIOTICS ANALYSIS ON INSTAGRAM ACCOUNTS @CRISTIANO, @JUSTINBIEBER, @LEOMESSI, AND @THEROCK) - Wendra Ajistyatama; Ahmad Mulyana (Universitas Mercu Buana, 2021)
Social media Instagram is a popular photo and video sharing application. Through sharing images on the app, influencers can promote or endorse products, brands and services to their followers. Influencers are also required to be creative in posting photos on Instagram for the sake of the beauty of the feed on their Instagram. Their success in promoting or assessing their reputation as influencers is usually manifested through the number of “Likes” received on photos posted on Instagram accounts. The question is what kind of fashion images are likely to be well received by their followers. This study uses the work of social semiotics Kress and van Leeuwen (1999&2006) to evaluate what types of photos tend to be liked by audiences and why they are liked. The analysis involved examining five different semiotic sources (i.e. distance from which the photo was taken, participant gaze (gaze), relationship between participants in the photo, participant's clothing and clothing color), followed by a qualitative analysis of preferred photographs, taking into account the particular context of the photo. The photo is like the identity described by the influencer, and the moment is described through the photo.